Faculty perceptions of academic librarians at the University of the Philippines Diliman - Visperas, Rizalyn S.; Santos, Herminia H. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2002)
This study sought to determine the perceptions of the faculty of the University of the Philippines (UP) Diliman College of Arts and Letters (CAL) and College of Social Sciences and Philosophy (CSSP) towards academic librarians. The respondents in this study were full-time and part time faculty of these two colleges during the second semester of the school year 2001-2002. Results of the study reveal that the faculty rate the librarians efficient enough in keeping the faculty informed on changes in the library; efficient in keeping the faculty informed of new publications in their respective disciplines; and in assisting them in searching for materials in their subjects of expertise. A majority also perceived that librarians in general contribute only 30 percent in the education of the students.
The faculty perceived librarians to be equal partners in the selection of library materials in the following subject areas: reference, general interest/casual readings, and inter-disciplinary subjects. On the other hand, the faculty thinks that they alone must be responsible in selecting library materials in course-related subjects and their research interests.
When it comes to the faculty perceptions on the librarians' role in the following library activities, the results show that the faculty rate the librarians above average in selection of appropriate reading materials; supervision of staff: and knowledge and skills in accessing remote databases. The faculty gives a high rating to the librarians' management of information resources. Majority of the faculty view librarians, as professional but do not recommend that they have faculty rank and status. A change in the misperceptions of faculty towards librarians could be realized only if the librarians themselves clearly define their roles as allies and partners in the educational process.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines,Diliman -- Faculty; College librarians -- Philippines -- Quezon City